2000
DOI: 10.1074/jbc.m002618200
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Screening of Mutations in Pmr1, the Yeast Secretory Pathway Ca2+/Mn2+-ATPase, Reveals Residues Critical for Ion Selectivity and Transport

Abstract: Thirty-five mutations were generated in the yeast secretory pathway/Golgi ion pump, Pmr1, targeting oxygen-containing side chains within the predicted transmembrane segments M4, M5, M6, M7, and M8, likely to be involved in coordination of Ca 2؉ and Mn 2؉ ions. Mutants were expressed in low copy number in a yeast strain devoid of endogenous Ca 2؉ pumps and screened for loss of Ca 2؉ and Mn 2؉ transport on the basis of hypersensitivity to 1,2-bis(2-aminophenoxy)ethane-N,N,N,N-tetraacetic acid (BAPTA) and Mn 2؉ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 24 publications
3
93
0
1
Order By: Relevance
“…Studies of the equivalent residue, Gly-310, in SERCA1a infer that mutations could sterically hinder ion binding, with the Ca 2ϩ affinity of the enzyme decreasing as the size of the substituted side chain in this position was increased (41). Recently, a mutation in the putative transmembrane segment M4 Ca 2ϩ -binding site of S. cerevisiae was shown to have a more deleterious effect on the transportation of Mn 2ϩ in comparison to Ca 2ϩ (17). This observation supports our conclusion that this region of the protein plays an important role in hSPCA1 Mn 2ϩ transport selectivity.…”
Section: Figsupporting
confidence: 80%
See 2 more Smart Citations
“…Studies of the equivalent residue, Gly-310, in SERCA1a infer that mutations could sterically hinder ion binding, with the Ca 2ϩ affinity of the enzyme decreasing as the size of the substituted side chain in this position was increased (41). Recently, a mutation in the putative transmembrane segment M4 Ca 2ϩ -binding site of S. cerevisiae was shown to have a more deleterious effect on the transportation of Mn 2ϩ in comparison to Ca 2ϩ (17). This observation supports our conclusion that this region of the protein plays an important role in hSPCA1 Mn 2ϩ transport selectivity.…”
Section: Figsupporting
confidence: 80%
“…Half-maximal inhibition of Ca 2ϩ uptake occurred at a Mn 2ϩ concentration approximately equivalent to the Ca 2ϩ concentration required for half-maximal stimulation of the uptake, indicating that the affinity of the hSPCA1d transport ATPase for Ca 2ϩ and Mn 2ϩ is approximately the same. In contrast, similar studies performed on S. cerevisiae PMR1 showed this latter protein to have a somewhat lower affinity for Ca 2ϩ than Mn 2ϩ (17). Conclusions drawn from the isotope fluxes were further verified by the results of phosphoenzyme studies, which indicated that maximal phosphoprotein formation from ATP was achieved at micromolar concentrations of Ca 2ϩ and Mn 2ϩ , demonstrating the high affinity nature of the binding sites.…”
Section: Figmentioning
confidence: 59%
See 1 more Smart Citation
“…The most likely route for ions to reach this site is through the cavity between M4 and M6. Indeed, this route is taken by hydrated Ca 2+ to reach a similarly positioned ion-binding site in SERCA (22) and mutations in residues of M4 and M6 block access of ions to the homologous ion-binding site in Pmr1p (21,27,28). Residue Q747 of SPCA1 is predicted to be at the cytoplasmic/membrane interface of M6 with an orientation that projects its side chain into the solvent accessible cavity between M4 and M6 ( Fig.…”
Section: Substitution Of Q747 With Alanine Increases Activity Of Spcamentioning
confidence: 99%
“…Not only is functional complementation powerful in predicting function, it is also useful in investigating how mutations affect activity. With PMR1 itself, a large number of site-directed mutations were made and rapidly screened for hypersensitivity to BAPTA and Mn 2ϩ (51,89). Liquid growth assays in a 96-well format are amenable to testing a range of inhibitor concentrations, and growth can be monitored by using a microplate reader for high-throughput screening of mutants.…”
Section: Secretory Pathway Ca 2؉ -Atpase Defective In Hailey-hailey Dmentioning
confidence: 99%